Analyzing Indonesian Students’ Needs for Virtual Drama Scripts: Bridging Climate Change Topic and Pancasila Profile Dimensions - Ermalati Putri; Rita Inderawati; Machdalena Vianty (Universitas Hamzanwadi, 2023)
In the Independent curriculum, it is essential to provide students with diverse learning materials that address global concerns like climate change while also aligning with personal and cultural dimensions, such as the Pancasila Student Profile. This study, conducted at Srijaya Negara High School in Palembang, Indonesia, aimed to understand students' needs for virtual drama scripts that incorporate both climate change and the Pancasila Student Profile themes. Insights were gathered from 36 tenth-grade students, their English teachers, and additional stakeholders through a mixed-methods approach, combining questionnaires and semi-structured interviews. The results highlighted a demand from students for more specific and contextually relevant materials. The integration of climate change and Pancasila themes in virtual drama scripts was found to enhance students' motivation in English learning, particularly with the inclusion of technology. Furthermore, these tailored scripts are believed to improve students' knowledge and awareness of both climate change and the values of Pancasila. This research paves the way for the development of virtual drama scripts that not only serve as English reading materials but also support broader educational initiatives in high schools.